Efek Perilaku Individu terhadap Kinerja Karyawan - Siwi Dyah Ratnasari; Tarimin Tarimin (Jurnal Administrasi Bisnis, 2021)
The purpose of this research is to see how work environment and competency affect performance of workers, with Behavior of an individual as an intervening variable. The data for this study was gathered using quantitative methods such as questionnaires. The participants in this study were all 87 employees of the Pasuruan Regency Transportation Office. Census technique was employed in the research sample. Smart PLS 3.0 was used to evaluate the data. The findings revealed that: (1) Work environment variables influenced performance of workers in a positive and significant way; (2) Behavior of an individual is influenced by the work environment in a positive and significant way; (3) Employee performance is influenced by competence in a favorable and meaningful way; (4) Individual conduct is influenced by competence in a positive and significant way; (5) Behavior of an individual has a positive and significant environmental impact; (6) The work environment has a positive and major impact on performance of workers through individual behavior, and competence has a positive and significant impact on employee performance through individual conduct; (7) Behavior of an individual is mediated by competence, This has a big and beneficial effect on performance of workers. Behavior of an individual has an impact on performance of workers due to competence. According to the findings, competency has the biggest impact on performance of workers e, therefore increasing employees' knowledge, abilities, and attitudes is necessary to support activities at the workplace. Workplace, competence, individual conduct, and performance of workers are some When thinking about the workplace, these are some of the terms that spring to mind.Tujuan dari penelitian ini adalah untuk melihat bagaimana lingkungan kerja dan kompetensi mempengaruhi kinerja karyawan, dengan perilaku individu sebagai variabel intervening. Metode kuantitatif melalui kuesioner digunakan untuk mengumpulkan data dalam penelitian ini. Semua Karyawan Dinas Perhubungan Kabupaten Pasuruan yang berjumlah 87 karyawan adalah populasi dalam penelitian ini. Sampel penelitian menggunakan sampel jenuh. Smart PLS 3.0 digunakan untuk mengevaluasi data. Temuan mengungkapkan bahwa: (1) pengaruh positif dan signifikan lingkungan kerja terhadap kinerja karyawan; (2) perilaku individu dipengaruhi oleh lingkungan; (3) pengaruh positif dan signifikan kompetensi terhadap kinerja karyawan; (4) pengaruh positif dan signifikan lingkungan kerja terhadap perilaku individu; (5) pengaruh positif dan signifikan perilaku individu terhadap kinerja karyawan; (6) melalui perilaku individu, pengaruh positif dan signifikan lingkungan kerja terhadap kinerja karyawan; (7) dimediasi oleh perilaku individu, kompetensi mempunyai pengarus positif dan signifikan terhadap kinerja karyawan. Pengaruh total antara kompetensi dengan kinerja karyawan dan perilaku individu sebagai variabel intervening merupakan hubungan partial mediation. Implikasi penelitian menunjukkan bahwa diperlukan peningkatan pengetahuan, keterampilan, atau sikap bagi karyawan upaya meningkatkan kinerja organisasi karena kompetensi memiliki pengaruh paling besar terhadap kinerja karyawan.